2005
DOI: 10.1136/gut.2004.058354
|View full text |Cite
|
Sign up to set email alerts
|

Long term failure of endoscopic gastroplication (EndoCinch)

Abstract: Introduction: Endoluminal gastroplication (EndoCinch; Bard) has been introduced as an endoscopic treatment option in gastro-oesophageal reflux disease (GORD) patients with promising short term results. However, little is known about the long term efficacy of endoscopic suturing. The aim of this study was to evaluate prospectively the long term outcome after EndoCinch. Patients and methods: A total of 70 patients treated with EndoCinch at a single referral centre were studied prospectively. All patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
8
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 39 publications
5
92
8
3
Order By: Relevance
“…In the sham-controlled study reported by Schwartz et al [48], endoscopy/gastroplication was performed only in patients of the active treatment group who had treatment failure, and hence the actual proportion of patients who have retention of stitches (or judged to be functional) is unknown in this group. However, retention of stitches seems to be a major problem reported with this technique [48, 52, 53]. Further studies are needed to confirm the above.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the sham-controlled study reported by Schwartz et al [48], endoscopy/gastroplication was performed only in patients of the active treatment group who had treatment failure, and hence the actual proportion of patients who have retention of stitches (or judged to be functional) is unknown in this group. However, retention of stitches seems to be a major problem reported with this technique [48, 52, 53]. Further studies are needed to confirm the above.…”
Section: Discussionmentioning
confidence: 90%
“…Loss of plications has been reported both with the knot technique [43] as well as with the clip device [52] used for anchoring the sutures, but seems to be more frequently with the latter. In the sham-controlled study reported by Schwartz et al [48], endoscopy/gastroplication was performed only in patients of the active treatment group who had treatment failure, and hence the actual proportion of patients who have retention of stitches (or judged to be functional) is unknown in this group.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are less invasive alternatives of laparoscopy. The Esophyx device [34], for the TIF method, which means Transoral Incisionless Fundoplication, is manufactured by EndoGastric Solution and allows the creation of a fundoplication esophagogastric of 2-3 cm thick, for circumferential extension of 270°, capturing the mucous tissue with 12 or more points of polypropylene suture. The device is used in combination with an endoscope flexible video, which provides the endoscopic visualization thoughout the operation.…”
Section: Techniques Of Endoscopic Fundoplicationmentioning
confidence: 99%
“…The percentage of patients who did not require PPIs decreased from 52% at 2 months to only 20% at 1 year and even more patients had evidence of reflux esophagitis at 1 year (56 vs. 41% at inclusion). Schiefke et al [66] also reported that 18 months after EndoCinch, 80% of patients were considered treatment failures as their heartburn symptoms did not improve or PPI usage exceeded 50% of the initial dose. There were no significant changes in 24-hour esophageal pH monitoring score or LES pressure while median LES length slightly increased (3.0 to 3.2 cm; p < 0.05).…”
Section: Selection Criteria For Endoscopic Therapymentioning
confidence: 99%